Technological tools to measure customer satisfaction - Guaman Carrasco, Wilson Eduardo; Barrera Basantes, Ruth Laura; Mora Piña, Paulina Fernanda; Freire Quintanilla, Mesías Heriberto (mktDESCUBRE; Vol 1 No 1 (2020): InnovaEc 2019 Special Edition Congress, 2020)
This research focuses on the relationship between the use of technological tools and the effectiveness in measuring customer satisfaction. In the dynamic business environment, customer satisfaction has become an important component for constant measurement. A big impact in the follow-up of the satisfaction of the clients with the panorama of services could cause a change of brand and increase the rate of attrition of a brand, which is strategically unacceptable. As a result, brands must develop an awareness of different technologies, technologies, technology, smart technology, and the service landscape with maximum efficiency. In addition, it is important that the brands are applied in the implementation of the implemented tools. The element of sustainability plays a necessary role in maintaining competitive advantage in uncertain industrial conditions. The integration of the technological tools is important to keep track of the satisfactory changes and avoid the significant loss of the customer base.